Análisis de la fotografía en blanco en negro de Sebastião Salgado la Amazonia - Contreras Peralta, Kelvin Fernando (2023)
This research work has the purpose of knowing more about black and white photographs in order to analyze Sebastião Salgado's images and to demonstrate that through this type of photos it is also possible to express and appreciate what the photographer wants to convey. Through his works, over time these works have a great meaning in life since they show many realities in the world and although Salgado was criticized for his photos, they are still something that many appreciate. Black and white photography as it is also called monochrome where there is no color but only gray and black, it can be said that it is the representation of the purest expression that exists; Through it, when taking an image, either from a look, it can reveal all the expression or drama of the photo. In 1827 Niepce was the one who managed to take a photograph through a heliography technique where he used silver chloride in a camera obscura, but in addition to this the painter Louis J. Daguerre achieved the beginning of photography by taking the first steps to perfect the photography art. For this type of images, it must be taken into account that the essential of these images is to be able to choose scenes where color is not dominant. For this type of photographs, one can select those that express the sensation of stillness, aggressiveness, peace, sensuality, among other. In these images you have to know how to use composition and contrast to convey emotions in this type of photos. Therefore, this research project with a qualitative approach because it sought to analyze black and white photography, through materials such as an observation sheet and interview, where relevant results were obtained.